Socio-Economic Conditions Abrasion Coastal Communities Affected In Kanagarian Sasak Sasak District of West Pasaman Pasisia domains - Rahmayani, Rahmayani; Drs. Bakaruddin M.S, Drs. Bakaruddin M.S; Juita S.Pd, M.Si, Erna (Pendidikan Geografi, 2014)
ABSTRACTThis study aims to obtain data and information are: 1) the fulfillment of the basic needs of communities affected coastal erosion. 2) the level of public health conditions affected by coastal erosion. 3) the condition of the level of income of the people affected by coastal erosion. 4) housing conditions of people affected coastal erosion. This research is descriptive, which became the study population is affected by coastal erosion Jorong in Kanagarian Sasak consisting of Jorong Pasa cottage with Lamo. The sample of respondents was taken by total sampling totaled 148 households, respondents number of people affected by coastal erosion in Jorong cottage and Pasa Lamo Kanagarian Sasak.The results of this study found: 1) the fulfillment of the needs of communities affected by coastal erosion in Kanagarian Sasak Less well (56.79%). 2) The health condition of the affected communities in coastal erosion Kenagarian good enough Sasak (69.65%). 3) Conditions income communities affected by coastal erosion in Kenagarian Sasak Less well (62.75%). 4) The condition of public housing in the affected coastal erosion Kenagarian Sasak Less well (60.3%).